A Mukaiyama–Claisen Approach to 3,5-Diketo Esters - Wang, Qinggang; List, Benjamin (Synlett, 2015)
A thermally promoted synthesis of 3,5-diketo esters via a Mukaiyama–Claisen reaction of 4H-1,3-dioxin-4-one derivatives with silyl enolates has been developed. The desired oligocarbonyl compounds were obtained with moderate to good yields.
Keywords: 3,5-diketo esters; Mukaiyama–Claisen reaction; thermal reaction; silylated nucleophiles